1983
DOI: 10.1161/01.cir.67.2.434
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a reentry circuit in the common type of atrial flutter in man.

Abstract: SUMMARY To investigate the mechanism of atrial flutter (AF) in humans, we studied 13 patients during episodes of spontaneous common AF, with simultaneous multiple atrial endocavitary recordings and atrial programmed stimulation. In all patients, low paraseptal atrial activation preceded high right atrial activation, and the latter preceded mid-or low lateral right atrial activation (recorded in five patients). Programmed atrial stimulation resulted in early reset of the AF cycle, with an unchanged poststimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(17 citation statements)
references
References 24 publications
(6 reference statements)
0
15
0
2
Order By: Relevance
“…Typical atrial flutter is a macroreentrant atrial tachycardia with electrical activation through the cavotricuspid isthmus (CTI) 1 , which is a critical part of this circuit 1 . According to the electrophysiological mechanism and the anatomical structure, atrial flutter is classified as typical or reverse-typical depending on, respectively, the counterclockwise or clockwise direction of the activation wave through the CTI 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Typical atrial flutter is a macroreentrant atrial tachycardia with electrical activation through the cavotricuspid isthmus (CTI) 1 , which is a critical part of this circuit 1 . According to the electrophysiological mechanism and the anatomical structure, atrial flutter is classified as typical or reverse-typical depending on, respectively, the counterclockwise or clockwise direction of the activation wave through the CTI 2 .…”
Section: Introductionmentioning
confidence: 99%
“…2 The cavotricuspid isthmus is an essential part of the typical AFL circuit and has been identified as the area of slow conduction. 3,4 To date, it has been assumed that activation of typical AFL rotates around the TA, and it is considered that an electrical barrier to transverse conduction exists throughout the posterolateral area of the RA, from the SVC to the IVC. 5,6 However, it has been shown recently that blocking does not occur in that entire region.…”
mentioning
confidence: 99%
“…6 The diagnosis of rapid atrial flutter was based on (1) organized, rhythmical atrial waves (variation in cycle length <10%), (2) an atrial rate of spontaneous flutter above 320 beats per minute, and (3) in case the arrhythmia was induced by rapid atrial pacing performed to interrupt spontaneous common atrial flutter, any type of arrhythmia was considered rapid atrial flutter that showed organized electrical activity as an atrial rate above that of the original arrhythmia. The morphology of the F wave was not considered discriminant.…”
Section: Methods and Resuls Atrial Interval Variations Of 17 Epi-mentioning
confidence: 99%